Invasive floating water weeds – killing life and commerce - Ajuonu, O.; Tamò, Manuele; Neuenschwander, Peter; Toko, M.; Beed, Fenton D.; Hounkpe, C. (International Institute of Tropical Agriculture, 2010)
Weeds by definition are plants that grow in the wrong place. When their seeds or other plant parts are transported to other regions where their natural enemies are absent, they can multiply unhindered. Indigenous plants, especially those that are adapted for invading disturbed areas, can also become weeds. The first category is a particularly good target for classical biological control. Insects, mites and micro-organisms that feed on them are imported from their original area and released against the new invader. Against indigenous plants however, biological control is far less promising. By the end of 1980s, many of the water bodies in West Africa were invaded by alien plant species considered to be among the world’s worst aquatic weeds: water hyacinth Eichhornia crassipes, water lettuce Pistia stratiotes, and water fern Salvinia molesta. They were accidentally or deliberately introduced as ornamentals or for use in aquariums from their native range South America to many parts of the world where they have become invasive.